Legalizing abortion for rape victims in Malaysia / Nurul Farhana Zaidi … [et al.] - Zaidi, Nurul Farhana; Fairous, Syafieqa; Roslan, Anith Arina; Syed Ahmad Kamal, Syarifah Zunierah (2014)
The purpose of this research is a matter to legalize abortion for rape victims in Malaysia. The research started when we realised that S312 of the Malaysian Penal Code (Act 574) only permitted abortion if the continuance of the pregnancy would place the life of the mother at risk and it must be confirmed by a medical practitioner registered under the Medical Act 1971. This provision has come to an issue of injustice as the right of women to seek for abortion has been deprived especially for the rape victims. The right to obtain an abortion should be examined in order to see whether such right would fall as an absolute right of women on the basis of morality and religious views. In result of this research, many States have actually acknowledged such right to get an abortion for the rape victims.